Foreign Aid and Enlightened Leaders - Roland Hodler; Paul A. Raschky (Swiss National Bank, Study Center Gerzensee, 2010)
To study whether foreign aid fuels personal, regional and ethnic favoritism, we use satellite data on nighttime light for any region in any aid-recipient country, and we determine for each year and each country the region in which the current political leader was born. Having a panel with 22,850 regions in 91 aid recipient countries with yearly observations from 1992 to 2005, we compare the effect of foreign aid on nighttime light across regions. We find that in countries with poor political institutions, this effect is significantly higher in the region in which the current political leader was born than in other regions. This finding suggests that a disproportionate share of foreign aid ends up in the leader's birth region, and we argue that it supports the view that foreign aid fuels favoritism, broadly defined. We find no such difference in aid-recipient countries with sound political institutions.
Keywords: C23; D73; F35; O11; 330; Foreign aid; Political leaders; Favoritism; Political institutions; Entwicklungshilfe; Regierungschef; Politisches System; Welt